A “patient as educator” intervention: Reducing stigmatizing attitudes toward mental illness among medical students - Beatriz Atienza-Carbonell; Beatriz Atienza-Carbonell; Helena Hernández-Évole; Vicent Balanzá-Martínez; Vicent Balanzá-Martínez; Vicent Balanzá-Martínez (Frontiers in Public Health, 2022)
IntroductionThis pre-post quasi-experimental pilot study aimed to assess the degree of stigma toward mental illness and whether a single, direct-contact “patient as educator” intervention with people with mental illness can reduce the degree of stigma among medical students.MethodsAll second-year medical students from the University of Valencia were invited to voluntarily complete the Community Attitudes Toward the Mentally Ill (CAMI), Reported and Intended Behavior Scale (RIBS), and Mental Health Knowledge Scale (MAKS) questionnaires before and after participating in the formal medical psychology course. A “patient as educator” workshop with expert patients was organized in the middle of the semester. A total of 127 students completed the survey; 20 students participated in the workshop (workshop group), and the remaining 107 students only took the formal educational course, forming the control group.ResultsAt baseline, the groups were demographically matched and did not differ in the components of stigma or knowledge of mental illness. After the intervention, a greater reduction in the CAMI subscales of authoritarianism and social restriction was observed in the workshop group than in the control group. In the workshop group, scores for the benevolence subscale of the CAMI decreased more among women than men. In the control group, scores for the authoritarianism and benevolence subscales of the CAMI increased and decreased significantly more, respectively, in women than men. No significant changes were observed in scores for the RIBS at post-intervention in either group.DiscussionThe results of this pilot study suggest that a brief, direct-contact intervention in addition to formal medical education may further help reduce stigmatizing attitudes during the first years of medical school.